Variation in growth of peanut plants under drought stress condition and in combination with paclobutrazol and ABA - Karthishwaran, R. Somasundaram, B. Sankar, P. Gopinathan, K. (Current Botany, 2016)
Â Â Â Â Â Â Â Â Â Â Â Economically important oilseed crop peanut (Arachis hypogaea L. TVM-2) belonging to the family Fabaceae was selected for the present investigation. Field experiments were conducted to identify the variation under drought stress, paclobutrazol, and abscisic acid, and their combination on the growth of peanut plants. Drought stress decreased the morphological parameters like root length, stem length, total leaf area, fresh and dry weight on 40, 60 and 80 days after sowing (DAS) when compared to control. The paclobutrazol (PBZ) and abscisic acid (ABA) treatment to the drought stressed plants increased all the parameters when compared to drought stressed plants. PBZ treatment increased the root length when compared to control, while decreased the stem length and leaf area. ABA treated plants decreased root length, while increasing the stem length and leaf area when compared to control. Fresh and dry weight decreased in drought stressed plants when compared to control. PBZ and ABA to the drought stressed plants increased the fresh and dry weight. PBZ and ABA treatments decreased the fresh and dry weight when compared in the unstressed plants..